Recent Advances in Green Synthesis, Characterization, and Applications of Bioactive Metallic Nanoparticles - Shabaaz J. P. Begum; S. Pratibha; Janhvi M. Rawat; Divya Venugopal; Prashant Sahu; Abhilash Gowda; Kamal A. Qureshi; Mariusz Jaremko (Pharmaceuticals, 2022)
Nanoparticles (NPs) are elements derived from a cluster of atoms with one or more dimensions in the nanometer scale in the range of 1–100 nm. The bio nanofabrication of metallic NPs is now an important dynamic area of research, with major significance in applied research. Biogenic synthesis of NPs is more desirable than physical and chemical synthesis due to its eco-friendliness, non-toxicity, lower energy consumption, and multifunctional nature. Plants outperform microorganisms as reducing agents as they contain large secondary biomolecules that accelerate the reduction and stability of the NPs. The produced NPs can then be studied spectroscopically (UV-Visible, XRD, Raman, IR, etc.) and microscopically (SEM, TEM, AFM, etc.). The biological reduction of a metallic ion or its oxide to a nanoparticle is quick, simple, and may be scaled up at room temperature and pressure. The rise in multi-drug resistant (MDR) microbes due to the immoderate use of antibiotics in non-infected patients is a major cause of morbidity and mortality in humans. The contemporary development of a new class of antibiotics with different mechanisms of action to kill microbes is crucial. Metals and their oxides are extremely toxic to microbes at unprecedentedly low concentrations. In addition, prevailing infections in plants and animals are raising significant concerns across the globe. NPs’ wide range of bioactivity makes them ideal antimicrobial agents in agricultural and medical fields. The present review outlines the synthesis of metallic NPs from botanicals, which enables the metals to be in a stabilized form even after ionization. It also presents a valuable database on the biofunctionalization of synthesized NPs for further drug development.